The effects of income on health: Evidence from lottery wins in Singapore - KIM, Seonghoon (Institutional Knowledge at Singapore Management University, 2021)
We estimate the causal effects of household income on self-reported health status by exploiting random variations in the amount of lottery prizes won. We find that a S$10,000 (US$7,245) increase in income via lottery wins improves individuals’ health by a standard deviation of 0.18. As possible mechanisms, we find that lottery wins increase household consumption spending and improve overall life satisfaction, but do not change healthcare spending, labor supply, and risky health behavior. Previous studies, which focused on the health effects of lottery prizes in Western European countries with strong social safety nets, do not find positive effects other than those on mental health. By contrast, the current study contributes to the literature by providing new evidence of the positive health effect of income via lottery wins in a country without strong social safety nets.